A porous hybrid material based on calixarene dye and TiO2 demonstrating high and stable photocatalytic performance. Issue 34 (13th August 2019) - Chen, Yi-Fan; Huang, Jian-Feng; Shen, Min-Hui; Liu, Jun-Min; Huang, Li-Bo; Zhong, Yu-Hui; Qin, Su; Guo, Jing; Su, Cheng-Yong
Abstract : A facile strategy to prepare a robust porous hybrid material (HO-TPA-TiO2 ) is presented by combining TiO2 with calixarene dye, HO-TPA, through a simple sol–gel method, offering efficient and persistent dual-function photocatalytic activities. Abstract : A highly robust hybrid material based on calixarene dye (HO-TPA ) and titanium dioxide with a micro/mesoporous structure and a large surface area (denoted asHO-TPA –TiO2 ) has been prepared by a facile sol–gel method. When Pt nanoparticles (Pt NPs) or fac -[Re(4, 4′-disphosphonic acid-2, 2′-bipyridine)(CO)3 Cl] (ReP ) as co-catalysts are introduced onto the hybrids, respectively, the two hybrid systems can display dual-functional photocatalytic properties. Under visible-light irradiation, the optimized Pt/HO-TPA –TiO2 system exhibits high hydrogen production activity (618.3 mmol g −1 h −1 based on Pt mass) and performs with excellent stability even after being used for 15 times (a turnover number of 6417 after 75 h). On the other hand, the optimumReP /HO-TPA –TiO2 material displays persistent photocatalysis of CO2 reduction to CO and gives a turnover number of 534 over 26 h (854.4 mmol g −1 based onReP mass), which is one of the highest among all the reported heterogeneous catalytic systems under visible light. The high activity and stability of theHO-TPA –TiO2 based hybrid materials can be attributed to the stable coordination linkage and efficient electron transfer betweenHO-TPA and micro/mesoporous TiO2 . The current study offers inspiration for the design and application of new multi-functional organic–inorganic hybrid systems for efficient photocatalysis.